The Utilization of Arabic Language Animated Video Media on Students' Speaking Skills - Octa Syakila Salsabila; Surya Hidayat; Muhammad Khatami; Abdurrasyid Abdurrasyid (Journal of Arabic Literature, Teaching and Learning, 2025)
This research aims to describe the effectiveness of utilizing Arabic language animated video-based learning technology on students' speaking skills at Islamic Junior High School in Indonesia. The study adopts a qualitative approach with a case study method. Data collection techniques include direct observation of the utilization of Arabic language animated video media and in-depth interviews with informants. The qualitative approach was chosen to provide a deep understanding of teachers' and students' experiences and perspectives regarding the use of Arabic language animated video-based learning media. Based on data analysis, the research concludes that the use of technology media significantly benefits in improving students' Arabic speaking skills at Islamic Junior High School in Indonesia. Through this learning media, teachers can present learning materials in a more engaging and interactive manner, which directly captures students' interest and attention. Furthermore, Arabic language animated video media also enhances students' motivation to learn and speak Arabic.